2011
DOI: 10.1093/ecam/nep144
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Activity of Trichilia catigua Hydroalcoholic Extract: New Evidence on Its Dopaminergic Effects

Abstract: Trichilia catigua is a native plant of Brazil; its barks are used by some local pharmaceutical companies to prepare tonic drinks, such as Catuama. The present study was addressed to evaluate the effects of T. catigua hydroalcoholic extract in mouse nociception behavioral models, and to evaluate the possible mechanisms involved in its actions. Male Swiss mice were submitted to hot-plate, writhing and von Frey tests, after oral treatment with T. catigua extract (200 mg kg−1, p.o.). The extract displayed antinoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 56 publications
0
15
0
2
Order By: Relevance
“…Commercially available preparations containing Trichilia catigua have been shown to display relaxant actions in Corpus cavernosum strips from rabbits (Antunes et al, 2001), and to present antinociceptive (Viana et al, 2009) and anti-inflammatory (Quintão et al, 2008) properties. In 2005, Campos et al have demonstrated antidepressant-like effects for Trichilia catigua hydroethanolic extract in rodents submitted to the forced swimming test (FST).…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available preparations containing Trichilia catigua have been shown to display relaxant actions in Corpus cavernosum strips from rabbits (Antunes et al, 2001), and to present antinociceptive (Viana et al, 2009) and anti-inflammatory (Quintão et al, 2008) properties. In 2005, Campos et al have demonstrated antidepressant-like effects for Trichilia catigua hydroethanolic extract in rodents submitted to the forced swimming test (FST).…”
Section: Introductionmentioning
confidence: 99%
“…The species has been little studied in some animal trials, which suggest antinociceptive and antidepressant activity. The antidepressant activity was associated with modulation of the serotonergic and dopaminergic systems [13, 53, 54]. …”
Section: Resultsmentioning
confidence: 99%
“…Other species also described as catuaba are Erythroxylum vacciniifolium Mart., Erythroxylaceae, and Tetragastris catuaba Soares da Cunha, Burseraceae, to mention a few (Lorenzi & Matos, 2002). Some studies suggest a possible analgesic and antidepressant effect for the Trichilia catigua mediated by dopaminergic mechanisms (Campos et al, 2005;Viana et al, 2009), while rare are the studies on Anemopaegma arvense reported in the literature.…”
Section: Brazilian Plants With An Adaptogen Profilementioning
confidence: 99%